CRETACEOUS NA-ALKALINE MAGMATISM FROM THE MISIONES PROVINCE (PARAGUAY): ITS RELATIONSHIPS WITH THE PALEOCENE NA-ALKALINE ANALOG FROM ASUNCIóN AND GEODYNAMIC SIGNIFICANCE - Velázquez V.F.; Comin-Chiaramonti P.; Cundari A.; Gomes C.D.; Riccomini C. (My University, 2006)
Alkaline (sodic) volcanic rocks, i.e., ankaratrites-melanephelinites, basanites-tephrites, and phonolites, dated at 119 Ma and similar in composition to the 60-Ma plugs of the Asunción Province, occur in Eastern Paraguay and belong to the Misiones Province. The age relationships confirm that the youngest volcanic events in Eastern Paraguay, at the central westernmost side of the Paraná basin, are represented by alkaline rock types of sodic affinity emplaced in late Early Cretaceous and Paleocene times. This sodic magmatism contrasts with the Early Cretaceous alkaline (potassic) magmatism of the region, and it is associated in space and time with the Paraná basin tholeiites. Geological and geophysical results for Eastern Paraguay indicate transtensional tectonics, with a NE-SW regional extensional stress field. The geochemistry and Sr-Nd-Pb isotope systematics are consistent with a lithospheric mantle source(s) enriched in incompatible elements by metasomatic processes. Nd model ages suggest that these probably occurred during Meso- and/or Neoproterozoic times and may be regarded as precursors of both alkaline and tholeiitic magmas in Eastern Paraguay. Potential parents for the alkaline (sodic) liquids have been modeled in terms of small degrees of mantle partial melting. Multielemental plots of calculated mantle sources for these liquids from Asunción and Misiones contrast with the analog mantle sources for the Paraguayan alkaline (potassic) suite, confirming the view that popular geodynamic markers of this type remain implausible indicators of subduction. Our results support the view that the magma genesis and the emplacement of the alkaline magmatism in southeastern Paraguay, and even in northwestern Argentina and Bolivia, is related to and probably driven by reactivation of preexisting lithospheric discontinuities in the various South American blocks, which promoted local decompression melting of previously enriched mantle sources. © 2006 by The University of Chicago. All rights reserved.
Keywords: Cretaceous; Neoproterozoic; Eocene; Paleocene; Mesozoic::Cretaceous; Мезозой::Меловая; Precambrian::Proterozoic::Neoproterozoic; Докембрий::Протерозой::Неопротерозойская; Cenozoic::Paleogene::Eocene; Кайнозой::Палеоген::Эоцен; Cenozoic::Paleogene::Paleocene; Кайнозой::Палеоген::Палеоцен